Implementation of School-Based Management in Creating Excellent Schools - Riani, Feni Okta; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to learn more about the application of School-Based Management in creating a superior school at SD Negeri 01 Rantau Panjang, as well as the elements that helped and hindered the SBM process. The study employs qualitative methodologies. SD Negeri 01 Rantau Panjang was the site of this study. Observations, interviews, and documentation were used to gather data. The acquired data is analyzed using the phases of data gathering, data reduction, data presentation, and conclusion drawing. The principal, teachers, students’ parents, and the school committee were the focus of this investigation. From the findings of this study, it can be inferred that (1) school-based management is fairly good, starting with curriculum management and ending with special service management. (2) Internal and external variables in SD Negeri 01 Rantau Panjang assist the implementation of SBM. The implementation of SBM in SD Negeri 01 Rantau Panjang was hampered by both internal and external issues. Internal reasons include a lack of proper facilities and infrastructure, insufficient learning tools and media, a shortage of qualified teaching professionals on the job, and limited funding. External factors, such as the lack of involvement of parents of children who are still absent, as well as a lack of collaboration between the school and the corporate world.